Comparison of Language Ability and Speech Production BetweenConstraint Induced Aphasia Therapy and Standard Speech Therapy for Chronic Broca Aphasian After Stroke - Dian Kusumawati; Ratna D Haryadi (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : The objective of this research is to determine an effective speech theraphy methods on post stroke patient with chronic aphasia BrocaMethods :A randomized controlled trial involeved fourteen patients with Broca’s Aphasia post stroke that divided into 2 groups : Group I –7 patients underwent 2 weekly sessions of Constraint Induced Aphasia Therapy (CIAT), 5 times a week, one hour for each session. Group II – 7 patients underwent 3 weekly sessions of standard method speech therapy, 3 times weekly and one hour for each session upto 10 hours. All patients were examined using Communicative Activity Log (CAL) to evaluate language ability and Functional Independence Measurement (FIM), expression communication’s subtest toevaluate speech production. CAL and FIM were performed pre and post therapy sessions.Results : Language ability and speech production were are increasing after CIAT (p=0,015) and also in group of standard methods of speech therapy as well (p=0,016).Conclusions : CIAT and standard speech therapy methods significantly increase language ability and speech production in stroke patients with chronic Broca aphasia.Keywords : Constraint Induced Aphasia Therapy (CIAT), standard speech therapy methods, Broca’s Aphasia post stroke.